Kedewasaan Usia Perkawinan Perspektif Hadis Nabi Muhammad dengan Pendekatan Interkoneksitas Maslahah - Gaffar, Abdul; Rusdi, M Ali; Akbar, Akbar (Fakultas Syariah IAIN Purwokerto, 2021)
Indonesian Muslims have not maximally applied maturity of marriage age as an important aspect in obtaining marital success. Apart from the concept of maturity of diverse marriage age, divorces and many marital problems based on the immaturity of a married couple still rife in Indonesia. The government has even issued regulations related to the age of marriage through Law number 1 of 1974 that was revised by Law number 16 of 2019, which stipulates that marriage is limited to a minimum age of 19 years for the two brides. This article aims to find the concept of quality-oriented marriage age to complement the quantity-oriented idea as applied by the Indonesian government and as understood differently by Muslims based on the opinions of the scholars (Ã¢â‚¬ËœulamÃ„Â). This article abstracts the concept of the ideal age of marriage from the instructions of the Prophet Muhammad PBUH as the primary reference of Islamic teachings by discussing the hadÃ„Â«th using the maÃ¢â‚¬ËœÃ„ÂnÃ„Â« al-hÃŒÂ£adÃ„Â«Ã¡Â¹Â¡ analysis with three interpretation techniques namely textual, intertextual, and contextual interpretation to obtain comprehensive meaning. The results of the examination show that the hadÃ„Â«th requires the criteria for the maturity of the marriage age in the form of religious, physical, financial, and social maturity. These qualitative criteria fulfill the element of maqÃ„ÂÃ¡Â¹Â£id al-syarÃ„Â«Ã¢â‚¬Ëœah and are interconnected so that they should be actualized as a new basis in the formulation of policies related to the maturity of marriage age in Muslim societies.